Long‐term phosphite application maintains species assemblages, richness and structure of plant communities invaded by Phytophthora cinnamomi. (30th January 2018) - Barrett, Sarah; Rathbone, Damien
Abstract: The impact of the plant pathogen Phytophthora cinnamomi and the fungicide phosphite on species assemblages, richness, abundance and vegetation structure was quantified at three sites in Kwongkan communities in the Southwest Australian Floristic Region. Healthy and diseased vegetation treated with phosphite over 7–16 years was compared with non‐treated healthy and diseased vegetation. After site differences, disease had the greatest effect on species assemblages, species richness and richness within families. Disease significantly reduced cover in the upper and lower shrub layers and increased sedge and bare ground cover. Seventeen of 21 species assessed from the families Ericaceae, Fabaceae, Myrtaceae and Proteaceae were significantly less abundant in non‐treated diseased vegetation. In diseased habitats, phosphite treatment significantly reduced the loss of shrub cover and reduced bare ground and sedge cover. In multivariate analysis of species assemblages, phosphite‐treated diseased plots grouped more closely with healthy plots. Seven of 17 susceptible species were significantly more abundant in phosphite‐treated diseased plots compared with diseased non‐treated plots. The abundance of seven of 10 Phytophthora ‐susceptible species was significantly higher along transects in phosphite‐treated vegetation. Comparison of the floristics of healthy non‐treated with healthy‐treated plots showed no significant differences in species assemblages. Of 21 species assessed, three increased in abundance and only one decreased significantly in phosphite‐treated healthy plots. In three Kwongkan communities of the SWAFR, P. cinnamomi had a profound impact on species assemblages, richness, abundance and vegetation structure. There was no evidence of adverse effects of phosphite treatment on phosphorus‐sensitive species, even after fire. Treatment with phosphite enhanced the survival of key susceptible species and mitigated disease‐mediated changes in vegetation structure. In the absence of alternative methods of control in native communities, phosphite will continue to play an important role in the protection of high priority species and communities at risk of extinction due to P. cinnamomi .